Studies on seasonal variations in physico-chemical parameters of the Temple pond Nashik District (M.S.), India. - K, Tidame S; S, Shinde S (International Multidisciplinary Research Journal, 2012)
Present work focused on the seasonal variations in the physico-chemical parameters of the freshwater temple pond- Prayagtirth at Trimbakeshwar in Nashik district during summer, monsoon and winter. A total 15 parameters were analysed and their seasonal variation is discussed. The correlation matrix of the various physico-chemical parameters are computed and analysed.